2005
DOI: 10.1016/j.joca.2005.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the chondrosarcoma cell line SW1353 with primary human adult articular chondrocytes with regard to their gene expression profile and reactivity to IL-1β

Abstract: Our data characterize SW1353 cells as a cell line with only a very limited potential to mimic PHCs, though SW1353 cells can be of value to study the induction of protease expression within cells, a phenomenon also seen in chondrocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
116
0
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 138 publications
(127 citation statements)
references
References 38 publications
(34 reference statements)
6
116
0
5
Order By: Relevance
“…This suggests that the effect of LRCH1 on the pathogenesis of OA may be via an inflammatory- independent mechanism, possibly involving compressive stress. SW1353 cells have been used by other researchers for the investigation of OA-related pathways (32,33). Although it was not the optimal cell line for the experiments we performed, these observations are interesting and should be validated in followup experiments using models that are more appropriate.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that the effect of LRCH1 on the pathogenesis of OA may be via an inflammatory- independent mechanism, possibly involving compressive stress. SW1353 cells have been used by other researchers for the investigation of OA-related pathways (32,33). Although it was not the optimal cell line for the experiments we performed, these observations are interesting and should be validated in followup experiments using models that are more appropriate.…”
Section: Resultsmentioning
confidence: 99%
“…The SW1353 cell line was procured from American Type Culture Collection (Manassas, VA). Both SW1353 and HCS-2/8 cells were grown using the same methods as previously described (17,20).…”
Section: Methodsmentioning
confidence: 99%
“…To understand the observed intracellular localization of MATN3 in chondrosarcoma tissue, we compared the findings in PHCs with those in 2 well-characterized human conventional chondrosarcoma cell lines, SW1353, which shares little of the phenotypic traits of PHCs (20), and HCS-2/8, one of a few cell lines to retain most of the gene expression profile of differentiated chondrocytes (17,18). We were able to verify that the 3 cell types exhibited behavior similar to that described previously (Vincourt J-B, et al: unpublished observations).…”
Section: Localization Of Matn3 In Cartilaginous Tumorsmentioning
confidence: 99%
“…LG100268 (LG268) and the SW-1353 human chondrosarcoma cell line, a model system for proinflammatory cytokine induction of MMP production by chondrocytes (20)(21)(22). Our data showed that LG268 selectively inhibited the proinflammatory cytokine-induced upregulation of MMP-1 and MMP-13 by decreasing the transcription rate of these genes.…”
mentioning
confidence: 87%